STRATEGI MNEMONIC DALAM PEMBELAJARAN MATEMATIKA - Eliza Verdianingsih (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2020)
ABSTRACT Memory play an important role in education since it is one of the aspects that determine students’ achievement. One that indicates sucessful learning is when students can remember what the teachers has taught. Mathematics is a lesson that is related to other studies. Each study consists of definition, formula, theorem and algorithm. Students are ought to remember and understand them to solve mathematical problems. Therefore, strategy of teaching which can help students to remember and understand the lesson, specifically for mathematics is needed. Mnemonic is one of strategies that can answer that problems. The methodology that is used in this article is literature study to gain deeper understanding about mnemonic strategy, specifically mnemonic srategy in mathematics. This article explains definition, techniques and benefit of mnemonic strategy. Furthermore, it will also explain mnemonic strategy in mathematics education. KEYWORDS: memory, mnemonic strategy, mathematic education ABSTRAK Memori atau ingatan memiliki peranan penting dalam suatu proses pembelajaran, karena memori merupakan salah satu hal yang dapat menentukan prestasi belajar peserta didik. Semua proses pembelajaran tidak akan ada hasilnya jika peserta didik tidak mampu mengingat materi pelajaran yang telah diajarkan. Matematika merupakan salah satu materi pelajaran yang terdiri dari berbagai bidang kajian. Setiap bidang kajian matematika berisi berbagai macam definisi, rumus, teorema dan algoritma. Peserta didik harus mengingat dan memahami hal tersebut untuk menyelesaikan masalah matematika. Oleh karena itu diperlukan strategi pembelajaran yang dapat membantu peserta didik dalam mengingat dan memahami materi pelajaran, khususnya matematika. Strategi pembelajaran tersebut adalah strategi mnemonic. Metodologi dalam artikel ini adalah kajian literatur untuk menggali pengetahuan tentang strategi mnemonic, khususnya strategi mnemonic dalam pembelajaran matematika. Artikel ini membahas tentang pengertian, teknik-teknik, dan manfaat dari strategi mnemonic. Selain itu juga dibahas tentang strategi mnemonic dalam pembelajaran matematika. KATA KUNCI: memori, strategi mnemonic, pembelajaran matematika